Knowledge management process and audit firms' performance / Fathiah Hashim - Hashim, Fathiah (2014)
This academic exercise examines the relationship between knowledge management (KM) process and audit firm performance. The study deployed variables from previous literatures on KM process and firm performance (Fong & Choi, 2009; Massa & Testa, 2009; Ngah, Hoo, & Ibrahim, 2009). As knowledge is considered an intellectual capital for audit, it is essential to see the impact of KM process which includes knowledge creation and acquisition, knowledge transfer and sharing, knowledge storage and retrieval, knowledge application and knowledge protection as main providers to audit firm performance. This study conducted a basic investigation on the impact of KM process in the audit firms in Malaysia through the survey questionnaires which were distributed to 46 audit firms located in lohor, Melaka, Negeri Sembilan and Selangor. The statistical results from the sample revealed that KM process has a positive significant relationship to the audit firms' performance. The result further indicated that knowledge creation and acquisition is the main contributor to the audit firm performance. It may also benefit specific groups of people including audit professional staff, audit firms' management, as well as motivating them to enhance firm performance through the KM processes.